High resolution assessment of air quality and health in Europe under different climate mitigation scenarios - Enrico Pisoni; Stefano Zauli-Sajani; Claudio A. Belis; Sasha Khomenko; Philippe Thunis; Corrado Motta; Rita Van Dingenen; Bertrand Bessagnet; Fabio Monforti-Ferrario; Joachim Maes; Luc Feyen (Nature Communications)
Abstract Climate change mitigation policies lower greenhouse gas emissions and generally reduce fine particulate matter (P M 2.5) concentrations, hereby bringing health co-benefits. Yet, the spatial and distributional air quality co-benefits in Europe of such policies are not fully understood. Here, We quantify premature mortality from air pollution in 1366 regions of Europe for different scenarios obtained from the Coupled Model Intercomparison Project Phase 6. We model P M 2.5 concentrations at high spatial resolution and then combine it with population data and regional age structure and total mortality, to calculate attributable deaths. We find that the share of the European population meeting WHO (World Health Organization) guideline value for P M 2.5 could exceed 90% by 2100 under the most ambitious scenario, while less than 10% under the least ambitious one. Corresponding premature deaths in Europe would total 67,000 (95% CI: 13,000–141,000) per year by the end of the century compared to 282,000 (95% CI: 202,000–364,000).